The effect of pre-primary education on primary school performance - Samuel Berlinski; Sebastian Galiani; Paul Gertler (Institute for Fiscal Studies (IFS), 2006)
Although the theoretical case for universal pre-primary education is strong, the empirical foundation is weak. In this paper, we contribute to the empirical case by investigating the effect of a large expansion of universal pre-primary education on subsequent primary school performance in Argentina. We estimate that one year of preprimary school increases average third grade test scores by 8 percent of a mean or by 23 percent of the standard deviation of the distribution of test scores. We also find that preprimary school attendance positively affects student's self-control in the third grade as measured by behaviors such as attention, effort, class participation, and discipline.
Keywords: 330